Report on industrial attachment with Starhub - Natalia Filo Sutanto (2008)
This report is written to summarize 24 weeks of industrial training received by the author during the industrial attachment program with StarHub Pte Ltd. It encompasses the author?s involvement in four major projects of StarHub Pte Ltd, namely: GIS Data Capture, Sales of Plant Map Flowchart, Netcon Database Updating and Fibre Allocation User Guide.